DABCO-bis-CC: An Efficient Alternative to PCC - Saikia, Bishwajit (Letters in Organic Chemistry, 2018)
We have developed a new chromium based reagent ‘DABCO−bis-CC' for the straightforward oxidation of alcohols to corresponding carbonyl compounds with high efficiency. The present results demonstrate a broad range of alcohols including primary, secondary, aliphatic, benzylic and heterocyclic alcohols are tolerated as substrates at room temperature.
Keywords: chromium